2010
DOI: 10.1091/mbc.e10-02-0131
|View full text |Cite
|
Sign up to set email alerts
|

Plakophilin 2 Couples Actomyosin Remodeling to Desmosomal Plaque Assembly via RhoA

Abstract: The desmosomal armadillo protein plakophilin 2 (PKP2) regulates cell contact-initiated cortical actin remodeling through the regulation of RhoA localization and activity to couple adherens junction maturation with desmosomal plaque assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 71 publications
7
113
0
Order By: Relevance
“…There is evidence that the translocation of cytoplasmic non-membrane bound desmoplakincontaining particles to desmosomes is an actin-dependent process (Godsel et al, 2005). One possible mechanism whereby Rnd3 might regulate desmosomes is through RhoA-dependent regulation of the actin cytoskeleton and activation of RhoA has been shown to accelerate the initial translocation of desmoplakin I/II to desmosomes, although sustained RhoA activity compromised desmosomal maturation (Godsel et al, 2010). Consistent with this, inhibition of RhoA results in loss of desmosomes and keratinocyte dissociation (Waschke et al, 2006).…”
Section: Loss Of Rnd3 Expression Is Associated With Altered Colony Momentioning
confidence: 87%
See 1 more Smart Citation
“…There is evidence that the translocation of cytoplasmic non-membrane bound desmoplakincontaining particles to desmosomes is an actin-dependent process (Godsel et al, 2005). One possible mechanism whereby Rnd3 might regulate desmosomes is through RhoA-dependent regulation of the actin cytoskeleton and activation of RhoA has been shown to accelerate the initial translocation of desmoplakin I/II to desmosomes, although sustained RhoA activity compromised desmosomal maturation (Godsel et al, 2010). Consistent with this, inhibition of RhoA results in loss of desmosomes and keratinocyte dissociation (Waschke et al, 2006).…”
Section: Loss Of Rnd3 Expression Is Associated With Altered Colony Momentioning
confidence: 87%
“…Rnd3 is known to regulate RhoA activity through p190RhoGAP and the RhoA GEF Syx (Wennerberg et al, 2003;Goh and Manser, 2010). RhoA activity during the redistribution of desmoplakin I/II to desmosomes is not affected by p190RhoGAP (Godsel et al, 2010) but this still leaves the possibility that Rnd3 is regulating RhoA through Syx or through some unknown Rnd3 effector.…”
Section: Loss Of Rnd3 Expression Is Associated With Altered Colony Momentioning
confidence: 99%
“…This suggests that RhoA is involved in regulating not only adherens junctions but also in desmosome assembly. PKP2 was shown to regulate cortical actin rearrangement during junction formation (Godsel et al, 2010). These authors showed that in PKP2 knockdown cells activated RhoA failed to localize at intercellular interfaces after the cell -cell contact induction, implicating a role of PKP2 in the spatiotemporal control of RhoA during junction formation (Figure 2).…”
Section: Rho-signalingmentioning
confidence: 97%
“…The relocation of this complex to the membrane requires a properly organized actin cytoskeleton (Figure 2). In this context, RhoA localization at the site of developing desmosomes is necessary, which again is dependent on Pkp2 (Godsel et al, 2010).…”
Section: Mechanisms Regulating Desmosome Turnovermentioning
confidence: 99%